Wingate anaerobic test reliability on the velotron with ice hockey players - Bringhurst, R. F.; Wagner, D. R.; Schwartz, S. (The Journal of Strength and Conditioning Research, 2020)
This study evaluated the test-retest reliability of the Wingate Anaerobic Test (WAnT) performed on a Velotron electromagnetically braked cycle ergometer for power-trained athletes and assessed whether a familiarization trial was necessary to achieve high test-retest reliability. Twenty-one male ice hockey players (age 23.5 ± 4.7 years, mass 86.3 ± 16.6 kg, height 180.9 ± 7.4 cm) from a collegiate club team (Club = 10) and a recreational league (Rec = 11) performed three 30-second WAnTs within 2 weeks and with at least 24 hours between visits. Mean power (MP), anaerobic capacity, peak power (PP), anaerobic power, maximum revolutions per minute, and fatigue index were assessed. Resistance was 8.5% of the participant's body mass. The effect of time on power output was moderated (p < 0.001, eta2p = 0.24) such that a significant increase was observed after a practice trial, but not between subsequent trials for the Club players; no practice effect was observed among Rec players. Extremely high reliability (ICC1,1) was found between trials after excluding the practice trial (MP = 0.973, anaerobic capacity = 0.975, PP = 0.957, and anaerobic power = 0.890). Club players achieved higher outputs despite no significant differences in body size or age compared with Rec players. Ice hockey players performing the 30-second WAnT on the Velotron electromagnetically braked cycle ergometer had highly reliable data, and using a familiarization trial is recommended to increase reliability and achieve higher power outputs.